The Use of English Learning Videos on Personal Tablets to Facilitate Primary Students' Literacy - Jumiatul Arpian (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to determine the effectiveness of tablet use by utilizing learning videos to improve student literacy at SD Negeri 15 Woja. The population of this study ranges from low to high-grade students (III & IV) at SD Negeri 15 Woja, which consists of 20 students. Each student from grades I to VI took 10 students, who were the primary samples in the implementation of this study. This research uses qualitative research methods. Furthermore, the research instruments used in this study are direct in-class observations containing video recordings and other supporting data such as activity documentation, researcher diaries, and additional website resources. After the data is analyzed using qualitative analysis, it can be concluded that using technological media in the form of learning videos effectively encourages students of SD Negeri 15 Woja to carry out literacy activities in different ways. The statement is corroborated by some of the data attached to the study.